2021
DOI: 10.5551/jat.55889
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial Calcification is Predictive for Hemorrhagic Transformation and Prognosis After Intravenous Thrombolysis in Non-Cardioembolic Stroke Patients

Abstract: Hemorrhagic transformation is the major complication of intravenous thrombolysis. Calcification is used widely as an imaging indicator of atherosclerotic burden and cerebrovascular function. The relationship between intracranial calcification and hemorrhagic transformation has not been explored fully. We aimed to identify and quantify calcification in the main cerebral vessels to investigate the correlations between quantitative calcification parameters, hemorrhagic transformation, and prognosis. Methods: Acut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 40 publications
(56 reference statements)
1
16
0
Order By: Relevance
“… 3 , 4 Intracranial calcification is associated with the early progression or recurrence of stroke, coronary events, vascular deaths, 5 and hemorrhagic transformation in patients with noncardioembolic stroke. 6 Vertebrobasilar calcification in patients with ischemic stroke is a valid predictor for stroke recurrence and acute vascular disease. 7 Coronary artery calcification in patients with atrial fibrillation has increased the independent risk of stroke, 3 but carotid calcification is not associated with incident stroke.…”
mentioning
confidence: 99%
“… 3 , 4 Intracranial calcification is associated with the early progression or recurrence of stroke, coronary events, vascular deaths, 5 and hemorrhagic transformation in patients with noncardioembolic stroke. 6 Vertebrobasilar calcification in patients with ischemic stroke is a valid predictor for stroke recurrence and acute vascular disease. 7 Coronary artery calcification in patients with atrial fibrillation has increased the independent risk of stroke, 3 but carotid calcification is not associated with incident stroke.…”
mentioning
confidence: 99%
“…Two studies reported that calcification volumes of the intracranial carotid artery and vertebrobasilar artery were significantly associated with worse outcomes after intra-arterial revascularization therapies. 27 , 28 Yu et al 29 reported that calcification volume on the lesion side was associated with hemorrhagic transformation after intravenous thrombolysis. Therefore, the higher volume of vertebrobasilar artery calcification observed in DM patients may substantially influence the prognostication and treatment decision-making.…”
Section: Discussionmentioning
confidence: 99%
“…According to the histopathologically validated method using plain CT, calcification are of two types: intimal calcification and medial calcification ( Kockelkoren et al, 2017 ). This scoring model has been proved and used in many researches ( Compagne et al, 2018 , Kauw et al, 2021 , Yang et al, 2018 , Yu et al, 2021 ). The circularity, thickness, and morphology of calcification were recorded.…”
Section: Methodsmentioning
confidence: 99%